Chiral ligands evolution of ligand libraries for asymmetric catalysis - Diéguez, Montserrat (New directions in organic and biological chemistry, 2021)
Many new drugs on the market are chiral compounds, that is, they can exist in two non-superimposable mirror-image forms. Asymmetric catalysis encompasses a large variety of processes for obtaining such compounds. The performance of the catalyst in those processes largely depends on the ligand that makes up the catalyst. This book describes the most relevant ligand libraries for some key processes, including an overview of the state of art and the key mechanistic aspects that favor a high catalytic performance.Key Features:The book presents historical content from the time of discovery for each family of ligands.Provides a description of the synthetic route and the ligand library's application in various catalytic asymmetric reactionsSuitable as supplementary reading for courses targeting the design, synthesis and application of chiral catalysts, asymmetric catalysis and sustainable productionEdited by a distinguished scientist in the field, the book has a diverse audience including research groups in homogeneous catalysis, particularly asymmetric transformations